The shape of translation policy: a comparison of policy determinants in Bangor and Brownsville - González Núñez, Gabriel (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2019)
The idea that there is something scholars can call “translation policy” has existed since the very early days of the field. As studies continue to spring forward, new perspectives continue to help our understanding of how translation policy evolves. Generally speaking, these studies tend to look closely at the role that the authorities play in shaping translation policy. Such an approach has led to useful insights, and for the foreseeable future, it will probably continue to provide enriching perspectives. But oftentimes, translation policy takes shape in official domains as a response to factors outside the domains themselves. In other words, there are insights to be gleaned by looking beyond the official domains. For example, interesting perspectives may come from looking at broader historical and demographic determinants that help shape translation policy. In that spirit, this paper will consider translation policy in two different settings: Gwynedd (Wales) and Cameron (Texas). It will compare and contrast these two regions in terms of history and demography, where some surprising parallels can be found. Then the article will describe translation policies in both places, where some stark contrasts become immediately apparent. Then this paper will analyze these differences in terms of how the minority language is viewed in these regions.